Local integration of electrically conductive paths using an in situ x-y positioning system in selective laser sintering - Lindbüchl, Matthias; Drummer, Dietmar (AIP Conference Proceedings, 2024)
Additive manufacturing processes offer significant advantages over conventional processes. In particular, there are fewer limits to the design freedom of additive manufacturing processes. In contrast additive manufacturing processes also have disadvantages that must be taken into account. For example, highly filled material systems cannot be processed in additive manufacturing, especially in powder bed-based processes such as selective laser sintering. However, it has already been shown that manufacturing with low-filled material systems can succeed. So far, the main goal has been functionalization with a view to improving mechanical properties on a global scale. In this study, the functionalization possibility with regard to the generation of locally electrically conductive paths by means of an x-y positioning system is to be investigated. In addition to various material systems, copper and solder powders will be used for this purpose. The copper powder is mixed volumetrically with the polyamide 12 powder (PA12) used in the process before discharge to ensure process capability, while the solder powder is used unmixed. The powders are then fed into the nozzle intended for discharge. In order to investigate the influence of the track width on the electrical conductivity, the process parameters of the x-y positioning system are also varied. This allows for an active influence to be exerted on the track geometry in terms of its width. The adjustable parameters include above all the traversing speed, the adjustable height between the powder bed and the nozzle, and the frequency and amplitude of the piezo element. The deposited tracks, which are processed into individual layers in selective laser sintering, are examined by means of microscopy for geometric and morphological formation as well as the connection of the track to the individual layer. The morphological and light microscopic analysis is followed by the examination of the electrical conductivity.
CRIS-Team Scopus Importer:2025-02-04

Selective Laser Beam Sintering of Multiphase Systems - Lindbüchl, Matthias; Drummer, Dietmar (Progress in Powder Based Additive Manufacturing, 2025)
Multiphase systems are material systems consisting of at least two components. This can be a material system with two polymers (blend production) or a polymer with fillers. The use of multipolymer material systems aims to improve properties through synergistic effects, for example, ‘positive’ material properties of both polymers mixed together should improve the final component properties. The use of fillers in a polymer matrix, on the other hand, is aimed at functionalization and improvement, especially of the mechanical properties of the components. These two concepts are presented in the following chapte
CRIS-Team Scopus Importer:2025-05-30